Obtainment and characterization of nanocellulose from an unwoven industrial textile cotton waste: Effect of acid hydrolysis conditions - Maciel, Maísa Milanez Ávila Dias [UNESP] (2019)
Cellulose nanocrystals (CNCs) have a promising application in many advanced products, such as biomedical applications and hydrogels. In this research, industrial cotton waste was treated using alkali and bleaching to eliminate hemicellulose, lignin, and other amorphous contents. The efficiency of these treatments was proven by chemical compositions analysis, which showed an increase in cellulose percentage with the progression of treatments. Fibers were analyzed by X-ray diffraction, thermogravimetric, and Scanning Electron Microscopy (SEM). CNCs were then prepared by acid hydrolysis using different sulfuric acid concentrations (50 wt%, 60 wt% and 64 wt%) and two reactions time (60 min. and 75 min.) resulting in six CNCs suspensions. CNCs were analyzed by X-ray diffraction, thermogravimetric, zeta potential, and Transmission Electron Microscopy (TEM). CNCs obtained exhibited a good crystallinity index varying from 75 to 81% and thermal stability between 146 °C and 200 °C. TEM analysis showed that sulfuric acid concentration influenced in CNCs length (105 nm–5880 nm). By analyzing all results, the optimal parameters for acid hydrolysis were 64% (w/w) of acid concentration combined with 60 min. of reaction time. The preparation of CNCs in this work showed some prospects of using untraditional industrial cotton waste as an advanced material.